Short term polyculture of three cyprinid species under mid-hill conditions in Meghalaya, North-east India - Das, S. K.; Mahanta, P. (Indian Journal of Fisheries, 2025)
This study evaluated the performance of a low-input polyculture system using three cyprinid species viz., Cyprinus carpio, Labeo gonius and Barbonymus gonionotus under mid-hill conditions in Umiam, Ribhoi District, Meghalaya (900 m above mean sea level) during the post-monsoon winter period. These species were selected for mid-hill aquaculture due to their rapid growth, early maturity, simple seed production techniques and market demand. In six months, the system achieved a production yield of 1,350 kg ha⁻¹. C. carpio attained an average final weight of 207.09 g with a mean survival rate of 86.96%, while L. gonius and B. gonionotus reached average final weights of 154.48 and 189.12 g, with survival rates of 80.54% and 81.25%, respectively. Results of the study indicated that integrating the three species into polyculture systems can enhance fish production in small and seasonal village ponds in mid-hill regions.Keywords: Aquaculture, Barbonymus gonionotus, Cyprinus carpio, Fish production, Labeo gonius